Valuable black gold as a result of utilization of municipal solid waste - Choubey, Shweta (Recent Research in Science and Technology, 2014)
Municipal solid waste (MSW) compost is increasingly used in agriculture as a soil conditioner but also as a fertilizer. Municipal solid waste (MSW) is an unwanted byproduct of modern civilization. Composting is the simultaneous means of conversion of organic waste into valuable fertilizer. Compost is “black gold” in agriculture. Compost has the potential of being fertilizer thus it is increasingly used in agriculture as a soil amendment improving the physical and chemical properties of soil. Proponents of this practice consider it an important recycling tool since MSW would otherwise be landfilled and critics are concerned with its often elevated metal concentrations. Large amounts of MSW compost are frequently used in agriculture to meet crop nitrogen requirements and for the addition of organic matter. Municipal solid waste compost has also been reported to have high salt concentrations, which can inhibit plant growth and negatively affect soil structure. A review of relevant agricultural studies is presented as well as recommendations for improving MSW compost quality.